ABO antigen levels on platelets of normal and variant ABO blood group individuals. (3rd October 2019) - Xu, Xianguo; Xu, Fang; Ying, Yanling; Hong, Xiaozhen; Liu, Ying; Chen, Shu; He, Ji; Zhu, Faming; Hu, Wei
Abstract: Although differential expression of ABO antigens on platelets is related to recipients' platelet recovery and neonatal alloimmune thrombocytopenia in ABO-incompatible transfusion and pregnancy, the expression of ABO antigens on platelets in normal and variant ABO blood group individuals is rarely reported. Here, we analyzed the expression of ABO antigens on platelets in a cohort of 515 individuals with normal and variant ABO. The variants were also genotyped for ABO and/or FUT1 loci to distinguish inherited or acquired ABO variants. The results showed that ABO antigens expression on individual platelets was relatively stable during the storage period in vitro . The frequency of low-, moderate-, and high-expression phenotype in normal individual was 59.6%, 35.5%, and 4.9%, respectively. The platelets from para-Bombay and most inherited ABO subgroups express very low levels of ABO antigens, but the acquired ABO variants and the B3 subgroup express normal or abnormally high levels of ABO antigens on platelets. The data extend the information of antigens expression on platelets, which may help to improve the strategy of platelets transfusion.